2022
DOI: 10.3390/ijerph19095363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rural Clinical Placements on Intention to Practice and Employment in Rural Australia: A Systematic Review

Abstract: Background: Supporting the provision of clinical placement (CP) experiences in rural areas is a strategy used worldwide to promote the rural health workforce. While there is international evidence for this intervention in medicine, there is limited understanding of the influence of rural CP for nursing, midwifery, allied health, and dentistry health professions in Australia, which have received substantial federal investment. This review examined the relationship between rural CP and non-medicine health studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The RHMT program aims to improve the size and composition of the rural health workforce through a variety of mechanisms that include: targeted rural health research; initiatives that increase the participation of rural origin students in health courses and student exposure to quality rural (MM2‐7) placement experiences as part of their training 2 . These approaches have been shown to have a positive impact on rural workforce development over time, 3 and are supported by the growing body of literature which demonstrates that lived rural experience and quality rural placements are both precursors to rural health workforce participation 4,5 …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The RHMT program aims to improve the size and composition of the rural health workforce through a variety of mechanisms that include: targeted rural health research; initiatives that increase the participation of rural origin students in health courses and student exposure to quality rural (MM2‐7) placement experiences as part of their training 2 . These approaches have been shown to have a positive impact on rural workforce development over time, 3 and are supported by the growing body of literature which demonstrates that lived rural experience and quality rural placements are both precursors to rural health workforce participation 4,5 …”
Section: Introductionmentioning
confidence: 97%
“…2 These approaches have been shown to have a positive impact on rural workforce development over time, 3 and are supported by the growing body of literature which demonstrates that lived rural experience and quality rural placements are both precursors to rural health workforce participation. 4,5 The RHMT program prescribes participating universities with minimum expectations for rural origin student enrolments in health courses. 2 Within rural medical training, participating medical programs are required to ensure at least 25% of the commonwealthsupported placements are for students of rural origin.…”
Section: Introductionmentioning
confidence: 99%
“…8 Research has found that students of rural-origin and students who undertook longer clinical training in a rural or remote setting were more likely to practice in rural or remote regions, particularly in medicine. 9,10 Further, having an interest in rural practice 8 and experiencing a positive student placement have also been found to influence intention to practice rurally. 6,8 However, the evidence relating to how clinical placements may contribute to rural and remote nursing and allied health practice in future remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 However, the evidence relating to how clinical placements may contribute to rural and remote nursing and allied health practice in future remains limited. In addition, although it is well-recognised that rural origin is a determinant for both intention for rural practice and actualised rural practice, 3,8,11,12 limited high-quality evidence exists for other determinants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation